Altitudinal distribution and diversity of insects in miombo woodlands in Inhamacari, Manica Province, central Mozambique. (3rd February 2020) - Nhiuane, Osório; Cuaranhua, Cláudio; Rombe Bandeira, Romana
Abstract: To evaluate the role of altitude on distribution pattern and diversity of entomofauna on miombo woodlands, four altitudes (850, 1, 000, 1, 250 and 1, 400 m) were selected in a characteristic mountainous forest of Inhamacari in Mozambique in July 2015. In each sampling altitude, a linear transect with 16 yellow pan traps spaced 2 m apart was established for insect capture. Capture results allowed assessment of insect distribution by determination of insect abundance and relative frequency. Insect diversity estimates were determined by Shannon–Wiener and Simpson indices. Altitude similarity was assessed by the Jaccard coefficient. The chi‐square test ( χ 0.05 2 ) was used to compare insect abundance and distribution along the altitudinal gradient. Altitude significantly affected insect abundance, relative frequency and distribution, with a nonlinear decrease with increasing altitude. Families Formicidae (Hymenoptera) and Cecidomyiidae (Diptera) were most dominant. Highest diversity and more families confined to unique altitudinal positions were found at 1, 250 m while the lowest diversity was observed at 1, 000 m.a.s.l. Among the altitudes, greater similarity was found between 1, 000 and 1, 400 m. In conclusion, altitude had a significant effect on insect family's distribution. However, further research is recommended in order to understand effect of vegetation composition and structure on insect diversity at different altitudes. Résumé: Afin d'évaluer le rôle de l'altitude sur le modèle de distribution et la diversité de l'entomofaune dans les forêts de miombo, quatre altitudes (850, 1 000, 1 250 et 1 400 m) ont été sélectionnées dans une forêt montagneuse caractéristique d'Inhamacari au Mozambique en juillet 2015. À chaque altitude d'échantillonnage, un transect linéaire avec 16 paniers jaunes espacés de 2 m a été établi pour la capture d'insectes. Les résultats de capture ont permis d'évaluer la répartition des insectes par la détermination de l'abondance des insectes et de la fréquence relative. Les estimations de la diversité des insectes ont été déterminées par les indices Shannon‐Wiener et Simpson. La similarité d'altitude a été évaluée par le coefficient Jaccard. Le test du chi‐carré (χ 2 0.05 ) a été utilisé pour comparer l'abondance et la distribution des insectes le long du gradient altitudinal. L'altitude a eu un effet significatif sur l'abondance, la fréquence relative et la distribution des insectes, avec une diminution non linéaire à mesure que l'altitude augmente. Les familles Formicidae (Hymenoptera) et Cecidomyiidae (Diptera) étaient les plus dominantes. La plus grande diversité et le plus grand nombre de familles confinées à des positions altitudinales uniques ont été observés à 1 250 m, tandis que la plus faible diversité a été observée à 1 000 m au‐dessus du niveau de la mer. Parmi les altitudes, une plus grande similarité a été trouvée entre 1 000 m et 1 400 m. En conclusion, l'altitude a eu un effet significatif sur la répartition des familles d'insectes. Toutefois, il est recommandé de poursuivre les recherches afin de comprendre l'effet de la composition et de la structure de la végétation sur la diversité des insectes à différentes altitudes.